On a method for estimating the solutions of quasilinear systems - Martynyuk, A.A. (Reports of the National Academy of Sciences of Ukraine, 2015)
To estimate the solutions of quasilinear systems of equations of perturbed motion, an estimation method is proposed on the basis of a nonlinear integral inequality.